USING A SIMULATION MODEL TO DETERMINE THE OPTIMUM NUMBER OF PILOTS IN AN AIR FORCE - Albertyn, M.; Trichard, S.D. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: The key objective is to present a simulation model to determine the optimum number of pilots in an air force. Background information about the simulation project, and a cursory description of the system under consideration, are provided. The Simul8 simulation software package, the basic concepts of the simulation model, the determination of adequate samples sizes, and simulation model verification and validation are discussed. Generic examples of typical results are shown, and conclusions about the simulation project are presented. AFRIKAANSE OPSOMMING: Die hoofdoelwit is om